Context, Character, and Civilisation: A Comprehensive Review of Mohammed and Mohammedanism - Khalid Hussain Mir; Prof. Hüseyin Çaksen (MAQOLAT: Journal of Islamic Studies, 2026)
This study offers a comprehensive analytical review of Mohammed and Mohammedanism, combining Reginald Bosworth Smith’s 1874 Royal Institution lectures and Emanuel Deutsch’s influential essay “Islam.” Through historical contextualisation, textual analysis, and comparative reflection, the review reassesses nineteenth-century European interpretations of the Prophet Muhammad (Pbuh), the Qur’an, and Islamic civilisation. The findings demonstrate that Smith and Deutsch pioneered a more balanced, evidence-based understanding that challenged prevailing polemical narratives. Their work highlights Muhammad’s (Pbuh) moral integrity, the Qur’an’s linguistic and literary uniqueness, and Islam’s substantial intellectual and civilisational contributions. This study situates their writings within broader Orientalist discourse while underscoring their lasting significance for modern scholarship on interreligious understanding, textual interpretation, and the historiography of Islam.